Absence of epithelial atypia in B3-lesions of the breast is associated with decreased risk for malignancy. (February 2017) - Mayer, Sebastian; Kayser, Gian; Rücker, Gerta; Bögner, Diana; Hirschfeld, Marc; Hug, Christiane; Stickeler, Elmar; Gitsch, Gerald; Erbes, Thalia
Abstract: Introduction: Lesions of uncertain malignant potential (B3) represent a heterogeneous group with an overall risk for malignancy of 9.85–35.1% after total resection. Positive predictive values (PPV) for malignancy vary depending on B3 subtype. The aim of this study was to evaluate the PPV for malignancy in B3 lesions and to determine the clinical significance of atypia-dependent sub-classification (a = without epithelial atypia; b = with epithelial atypia) of B3 into B3a and B3b and papillary lesions (PL) in PLa and PLb. Methods: 219 patients with histopathologically proven B3 lesions on core needle/vacuum-assisted biopsy who subsequently underwent diagnostic excision biopsy were included in this study. PPVs for malignancy were reported for B3 in general and all B3 sub-categories. Logistic regression analysis identified associations between B3-subgroups and outcome after excision biopsy as well as the impact of clinical and diagnostic findings on excision diagnosis. Results: The overall PPV rate was 10.0% (22/219). Excision histology exhibited a higher malignancy rate in PLb (2/7; PPV: 28.6%) than in PLa (6/127; PPV: 4.7%) (p = 0.057) and in B3b (12/50; PPV: 24.0%) compared to B3a category (8/165; PPV: 4.8%) (p < 0.001). Discussion: These findings support the necessity of B3 lesion sub-classification into B3a and B3b and of PL into PLa and PLb when considering epithelial atypia. The determination of atypia status represents a relevant factor in risk-stratification for clinical management of B3 lesions. Should future studies using the sub-classification of PL confirm these results, observation may be a safe option for the clinical management of patients with asymptomatic PLa lesions. Highlights: Clinical significance of atypia-dependent sub-classification of B3 into B3a and B3b and papillary (PL) lesions in PLa and PLb. Excision histology exhibited a higher malignancy rate in PLb than in PLa (p = 0.057) and in B3b compared to B3a category (p < 0.001). Atypia status represents a relevant factor in risk-stratification and clinical management of B3 lesions.